Exercise therapy improves mental and physical health in schizophrenia: a randomised controlled trial. (26th October 2012) - Scheewe, T. W.; Backx, F. J. G.; Takken, T.; Jörg, F.; van Strater, A. C. P.; Kroes, A. G.; Kahn, R. S.; Cahn, W.
Abstract : Objective: The objective of this multicenter randomised clinical trial was to examine the effect of exercise versus occupational therapy on mental and physical health in schizophrenia patients. Method: Sixty‐three patients with schizophrenia were randomly assigned to 2 h of structured exercise ( n = 31) or occupational therapy ( n = 32) weekly for 6 months. Symptoms (Positive and Negative Syndrome Scale) and cardiovascular fitness levels ( W peak and VO2peak ), as assessed with a cardiopulmonary exercise test, were the primary outcome measures. Secondary outcome measures were the Montgomery and Åsberg Depression Rating Scale, Camberwell Assessment of Needs, body mass index, body fat percentage, and metabolic syndrome (MetS). Results: Intention‐to‐treat analyses showed exercise therapy had a trend‐level effect on depressive symptoms ( P = 0.07) and a significant effect on cardiovascular fitness, measured by W peak ( P < 0.01), compared with occupational therapy. Per protocol analyses showed that exercise therapy reduced symptoms of schizophrenia ( P = 0.001), depression ( P = 0.012), need of care ( P = 0.050), and increased cardiovascular fitness ( P < 0.001) compared with occupational therapy. No effect for MetS (factors) was found except a trend reduction in triglycerides ( P = 0.08). Conclusion: Exercise therapy, when performed once to twice a week, improved mental health and cardiovascular fitness and reduced need of care in patients with schizophrenia.